Understanding NPL strategies for better workplace communication without the Jargon - "Kite,Neilson" (London, 2012)
Have you ever wondered how some people constantly achieve success in the workplace and in everyday life? Do you wish you knew more about how they think and behave? Understanding NLP will take you a step closer to sharing their success by showing you how to achieve personal and organizational goals. By applying the principles of NLP to the working environment and describing familiar situations in jargon-free language, it provides insights into interpersonal differences, selling and negotiation, influencing skills and the use of language. Further simplifying the key concepts of NLP and with greater emphasis on the differences between rapport and relationship and how both can be better developed and managed, Understanding NLP provides even more clarity and guidance in a simple and common sense way, helping you to make radical changes in the way you approach people, life and work.
Keywords: Neurolinguistic programming